Fish communities in adjacent seagrass and coral reefs in Babi Besar Island and Tinggi Island, Malaysia / Nina Ho Ann Jin - Nina Ho, Ann Jin (2018)
Tropical seagrass and coral reefs are highly complex and ecologically- important habitats that provide food and shelter for diverse marine fishes. It has been shown that habitat complexity attributes influence fish community structure in shallow marine habitats. Habitat complexity is defined as heterogeneity and architecture of the habitat, usually described by single-measure variables such as species richness, growth forms, percent cover, biomass, rugosity, substrate cover, canopy height and shoot density. The objectives of this study are (1) to characterise and compare fish communities; (2) to identify the habitat complexity attributes for fish density and species richness; and (3) to identify associations between habitat complexity and fish feeding guilds, in adjacent seagrass and coral reef habitats. Remote Underwater Video Station (RUVS) was used to document fish species and density within 2 x 2m quadrats on seagrass meadows (n=30) and adjacent coral reefs (n=31) in Tinggi Island and Babi Besar Island within the Sultan Iskandar Marine Park in Johor, Malaysia. From 1,098 minutes analyzed footage of RUVS, a total of 136 fish taxa were identified and enumerated from 1429 individuals sampled in the coral reefs, whereas 86 fish taxa were identified from 1005 individuals sampled in the adjacent seagrass meadows. Fish community data showed higher density of juvenile fish utilising the adjacent seagrass habitat as foraging ground. In contrast, coral reefs were mainly inhabited by adult fishes seeking refuge within the highly complex habitat. Additionally, there were 10 species of tropical marine fish identified as utilising both habitats which were mainly invertivores. These findings indicate the potential nursery function of the seagrass habitat and serve as important feeding grounds. To identify fish habitat relationship, multiple habitat complexity attributes were assessed for the seagrass meadows (percent cover, canopy height, shoot density, species richness) and coral reefs (percent cover, coral growth forms, substrate percent cover, rugosity, coral genus) using photo quadrat, chain, seagrass core and in situ measurement methods. Generalized Linear Models (GLMs) revealed seagrass percent cover and distance to adjacent habitat were important attributes for fish density and species richness in seagrass habitat, with total explained variance of 37% and 34% respectively. In coral reefs, the habitat complexity attribute of live coral cover explained 16% of the total variance in fish density; whereas 14% of the total variance in fish species richness was explained by the rubble percent cover. However, Canonical Correspondence Analysis (CCA) results illustrated no significant correlations between fish feeding guilds and habitat complexity attributes in both seagrass and coral reef habitats. In conclusion, habitat complexity and distance to adjacent habitat were found to be important in structuring fish communities in seagrass and adjacent coral reefs. These outcomes have important implications for fisheries and Marine Protected Area management in conserving the connected habitats of coral reefs and seagrass meadows to ensure the sustainable flow of ecosystem functions and services.